The Model of Educational Reconstruction – a Framework for Improving Teaching and Learning Science1 - Duit, Reinders; Gropengießer, Harald; Kattmann, Ulrich; Komorek, Michael; Parchmann, Ilka (Science Education Research and Practice in Europe, 2012)
To improve instructional practices – in schools, universities and in out of school settings has been a major concern of science education research and development. The intensive international debate on scientific literacy in the 1990s and the series of international monitoring studies like TIMSS and PISA in the 1990s and in the 2000s have fuelled this debate substantially. Various strands of science education research contribute to the stock of knowledge on more efficient means of teaching and learning science. The Model of Educational Reconstruction (MER) presented in this chapter provides a conception of science education research that is relevant for improving instructional practice and teacher professional development programs. The model is based on European Didaktik and Bildung (formation) traditions – with a particular emphasis on the German tradition. A key concern of the model is that science subject matter issues as well as student learning needs and capabilities have to be given equal attention in attempts to improve the quality of teaching and learning